Controlling Selectivity in Alkene Oxidation: Anion Driven Epoxidation or Dihydroxylation Catalysed by [Iron(III)(Pyridine‐Containing Ligand)] Complexes. Issue 19 (23rd August 2019) - Tseberlidis, Giorgio; Demonti, Luca; Pirovano, Valentina; Scavini, Marco; Cappelli, Serena; Rizzato, Silvia; Vicente, Rubén; Caselli, Alessandro
Abstract: A highly reactive and selective catalytic system comprising Fe(III) and macrocyclic pyridine‐containing ligands (Pc‐L) for alkene oxidation by using hydrogen peroxide is reported herein. Four new stable iron(III) complexes have been isolated and characterized. Importantly, depending on the anion of the iron(III) metal complex employed as catalyst, a completely reversed selectivity was observed. When X=OTf, a selective dihydroxylation reaction took place. On the other hand, employing X=Cl resulted in the epoxide as the major product. The reaction proved to be quite general, tolerating aromatic and aliphatic alkenes as well as internal or terminal double bonds and both epoxides and diol products were obtained in good yields with good to excellent selectivities (up to 93 % isolated yield and d.r .=99 : 1). The catalytic system proved its robustness by performing several catalytic cycles, without observing catalyst deactivation. The use of acetone as a solvent and hydrogen peroxide as terminal oxidant renders this catalytic system appealing. Abstract : Robust system : Controllable iron(III)‐catalysed alkene epoxidation or dihydroxylation reactions are performed by judicious choice of anion in [Fe(III)(Pc‐L)] catalysts (Pc‐L=pyridine‐based 12‐membered tetraaza‐macrocyclic ligands). The catalytic system proved its robustness by performing several catalytic cycles, without observing catalyst deactivation. The use of acetone as a solvent and hydrogen peroxide as terminal oxidant renders this catalytic system appealing.